“It is the life that has to be a work of art” Film-literary transposition of Naturaleza muerta con cachimba and Cachimba (2021)
The purpose of this paper is to compare the novel Naturaleza muerta con cachimba (1990) by Donoso and its corresponding filmoliterary translation Cachimba (2004) by Caiozzi. This comparison is presented based on Sánchez Noriega’s proposal founded on the additions, changesof characters, and the narrative/film order. To develop this approach, it is necessary to analyze Marcos Ruiz and Larco concerning the art. Thus, the importance of the temporal structure is recognized to understand the «existential metamorphosis» (Cid Hidalgo, 2019) of the protagonist, which allows us to reflect on the proposition that Marcos is an inverted reflection of Larco. Through the above, the falsity of the art world is revealed, which both the novel and the film present with humor, and how Marcos is a mirror reflection of Larco who, paradoxically, finds his true «I» when he metamorphoses into the artist thanks to the power of the pipe.